KEKOSONGAN HUKUM DAN IMPLEMENTASI KEWAJIBAN KERAHASIAAN AKTA OLEH CALON NOTARIS MAGANG (TINJAUAN PASAL 16A AYAT (2) UUJN-P) - Immanuela Christy Asa Suhir Sakri Putri; Athiyah Nurul Izza Rosyada; Jasmine Valery (Jurnal Privat Law, 2026)
The provisions of Article 16A paragraph (2) of the UUJN-P regulate the obligation of prospective notaries to maintain the confidentiality of deeds, but without being accompanied by strict sanctions for violations of this obligation in the UUJN-P. This study aims to identify the implementation of this article by prospective notaries. The research method used is normative juridical with a legislative and conceptual approach, as well as qualitative data analysis. The research found a legal vacuum in Article 16A paragraph (2) of the UUJN-P, namely the absence of concrete limitations regarding the scope of confidentiality of deeds that must be maintained by prospective notaries and the absence of juridical sanctions for violations of this obligation. In addition, the implementation of this article shows the application of a subjective confidentiality standard by prospective notaries due to the absence of limitations and strict sanctions, thus affecting prospective notaries in carrying out their obligations.